2014
DOI: 10.1186/1471-2180-14-96
|View full text |Cite
|
Sign up to set email alerts
|

The type III protein secretion system contributes to Xanthomonas citri subsp. citri biofilm formation

Abstract: BackgroundSeveral bacterial plant pathogens colonize their hosts through the secretion of effector proteins by a Type III protein secretion system (T3SS). The role of T3SS in bacterial pathogenesis is well established but whether this system is involved in multicellular processes, such as bacterial biofilm formation has not been elucidated. Here, the phytopathogen Xanthomonas citri subsp. citri (X. citri) was used as a model to gain further insights about the role of the T3SS in biofilm formation.ResultsThe ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 55 publications
6
41
0
Order By: Relevance
“…Notably, the ability of X. citri subsp. citri to form biofilms on abiotic surfaces, but not on plant tissue, is compromised by mutations in the type III secretion genes hrpB, hrpD, and hrpF (Zimaro et al, 2014). These observations suggest that E. psidii may require special conditions, probably mimicking the plant environ- of gene groups are predicted to be missing in the E. psidii strain IBSBF 435 draft genome (Hermenegildo et al, 2019), the absence of the investigated genes must be confirmed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Notably, the ability of X. citri subsp. citri to form biofilms on abiotic surfaces, but not on plant tissue, is compromised by mutations in the type III secretion genes hrpB, hrpD, and hrpF (Zimaro et al, 2014). These observations suggest that E. psidii may require special conditions, probably mimicking the plant environ- of gene groups are predicted to be missing in the E. psidii strain IBSBF 435 draft genome (Hermenegildo et al, 2019), the absence of the investigated genes must be confirmed.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, the ability of X. citri subsp. citri to form biofilms on abiotic surfaces, but not on plant tissue, is compromised by mutations in the type III secretion genes hrpB , hrpD , and hrpF (Zimaro et al , ). These observations suggest that E. psidii may require special conditions, probably mimicking the plant environment, for biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Given the observed differences in bacterial adherence to PVC and glass surfaces, we tested whether XccΔoprB shows impaired ability to adhere to the leaf surface, using CV staining to measure bacterial attachment. Xcc and XccΔoprBc were able to adhere to the leaf tissue, as observed previously for the wild‐type strain (Zimaro et al ., ), whereas the XccΔoprB mutant could not adhere, shown by the absence of CV staining (Fig. A,B).…”
Section: Resultsmentioning
confidence: 95%
“…This may be attributed to the fact that the lack of biofilm formation in the mutant strain probably triggers a deregulation of xanthan production, given that gumD expression is also increased in the mutant strain in order to compensate for the lack of the aggregative state. This has been observed previously in another Xcc mutant strain which was unable to form a biofilm, but showed increased xanthan production, as well as XanA and GalU overexpression, compared with Xcc wild‐type (Zimaro et al ., ), and also in an Xcc adhesin deletion mutant (Gottig et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the T3SS of the phytopathogen Xanthomonas citri subsp. citri is necessary for biofilm formation (21), and hyperactivity of the T3SS encoded by Salmonella pathogenicity island 1(SPI1) can mediate biofilm-like cell aggregation (22). Biofilms, highly structured microbial communities featuring bacterial cells attaching to a biotic or abiotic surface and embedded in a matrix (23,24), may neutralize the conventional antimicrobial effect and host defense and thus are difficult to eradicate (25).…”
mentioning
confidence: 99%